Contribuições dos makerspaces nos ecossistemas de inovação das cidades, na perspectiva das cidades educadoras - Oliveira, Shana Gonçalves de (2022)
Cities and their concepts have been changing over the years. Initially discussions about cities were based on relations of territorial domination, but today the city is seen and debated under different perspectives social, economic, technological and cultural. A large part of these discussions is imbricated in the economic development of cities and have as a backdrop the innovation ecosystem in which cities are inserted. Currently, innovation ecosystems are having more and more visibility, considering that they are constituted in the interactions of actors, who are strengthened in collaborative work in networks, whether national or international, based on issues related to innovation and territorial development. Among these actors, innovation habitats can be highlighted, one of which is makerspaces, which play a role as a connector between people and innovative ideas. They are fundamental actors to enhance the ecosystem. One of these innovation habitats are makerspaces, which play a role as a connector between people and innovative ideas. These spaces are considered as a new form of collaborative workspaces, in which people meet to work on personal and/or collective projects, using traditional and/or technological tools. They are consolidated as a relevant space for the city. The intentionality in the use of this spaces is one of the principles of the concept of educating cities, which has education as its core. It highlights the proposition of an education that goes beyond the walls of the school and brings together other spaces, promoting learning in children, young people, adults and elderly. The dissertation aims to analyze the main contributions of makerspaces in an ecosystem of innovation in cities, from the perspective of educating cities. For this it is necessary to propose a case study, analyzing data from five cities, three Brazilian capitals and two European cities. This is a predominantly qualitative research, of an applied nature, initially bibliographical in nature, with secondary data obtained through a literature review, followed by a survey of primary data, obtained through semistructured interviews with public managers and administrators of makerspaces, submitted to deductive content analysis. The result is the mapping of the public makerspaces of the analyzed cities, later it presents the contributions of the makerspaces that are directly linked to education, technology, digital inclusion, entrepreneurship, income generation and creativity, based on the “maker” culture, thus imbricated in the innovation ecosystem and objectively structured with the principles of educating cities